Proceedings of the 8th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design: Dri 2015
DOI: 10.17077/drivingassessment.1580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Listening to Music as a Function of Driving Complexity: A Simulator Study on the Differing Effects of Music on Different Driving Tasks

Abstract: Summary:Research in regards to music's effects on driving performance has been mixed. Previous research has found that music adds to mental workload. Other research has found that high mental workload is related to poorer driving performance in simulation. In this study, mental workload was manipulated by varying visual complexity and type of task (i.e., car-following or braking for unexpected obstacles). It was found that steering variance and delay in carfollowing response were reduced by music under low-wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…Specifically, in line with the inverted-U curve linking arousal to performance, previous research has found that background music increases arousal (Burkhard, Elmer, Kara, Brauchli, & Jäncke, 2018;Ünal et al, 2013) and that, when people are presented with an easy low-arousing task, the music can increase arousal resulting in better performance (Fontaine & Schwalm, 1979;Ünal et al, 2013). Contrarily, when people are presented with a difficult more arousing task, the music results in poorer performance, compatible with music increasing arousal to too high a level (Beh & Hirst, 1999;North & Hargreaves, 1999;Wang et al, 2015). In the current study, we used an easy low-arousing sustained-attention task-a version of the standard sustained-attention task called the Psychomotor Vigilance Task previously used by Unsworth and Robison (2016)-to imitate the boringness of real-life monotonous tasks and to maximise the potential for music to produce, via arousal, a beneficial effect.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Specifically, in line with the inverted-U curve linking arousal to performance, previous research has found that background music increases arousal (Burkhard, Elmer, Kara, Brauchli, & Jäncke, 2018;Ünal et al, 2013) and that, when people are presented with an easy low-arousing task, the music can increase arousal resulting in better performance (Fontaine & Schwalm, 1979;Ünal et al, 2013). Contrarily, when people are presented with a difficult more arousing task, the music results in poorer performance, compatible with music increasing arousal to too high a level (Beh & Hirst, 1999;North & Hargreaves, 1999;Wang et al, 2015). In the current study, we used an easy low-arousing sustained-attention task-a version of the standard sustained-attention task called the Psychomotor Vigilance Task previously used by Unsworth and Robison (2016)-to imitate the boringness of real-life monotonous tasks and to maximise the potential for music to produce, via arousal, a beneficial effect.…”
Section: Introductionmentioning
confidence: 61%
“…As previous research has suggested, arousal may mediate the relationship between background music and performance (Beh & Hirst, 1999;Cassidy & MacDonald, 2007;North & Hargreaves, 1999;Ünal et al, 2013;Wang, Jimison, Richard, & Chuan, 2015). Specifically, in line with the inverted-U curve linking arousal to performance, previous research has found that background music increases arousal (Burkhard, Elmer, Kara, Brauchli, & Jäncke, 2018;Ünal et al, 2013) and that, when people are presented with an easy low-arousing task, the music can increase arousal resulting in better performance (Fontaine & Schwalm, 1979;Ünal et al, 2013).…”
Section: Introductionmentioning
confidence: 70%
“…Los artículos recabados ascendieron a un total de 46 (Anexos 1 y 2). Con respecto al tipo de estudios, la distribución fue la siguiente: 42 estudios experimentales [1,2,6,8,9,10,11,12,13,14,17,18,19,20,21,22,23,24,25,28,29,30,31,32,33,34,35,37,39,40,41,42,43,44,45,46,47,49,51,50,52], un estudio de revisión [48], uno descriptivo [38], un estudio exploratorio [7] y un meta-análisis [26]. La productividad anual de las publicaciones registradas permitió hallar nueve publicaciones en el año 2012; seis publicaciones en 2013; cuatro publicaciones en el año 2019; tres publicaciones en los años 2007 y 2018; dos publicaciones en los años 1999, 2002, 2003, 2009, 2010, 2014, y 2016; y finalmente se halló una publicación en cada uno de los años…”
Section: Características De Los Estudiosunclassified
“…Por otro lado, algunos investigadores señalaron efectos adversos al considerar el tempo lento sobre la realización de ciertas tareas relacionadas a la conducción [42], y el tiempo demorado en recorrer una pista [22] [43] [44]. En contraposición a esto, diversos estudios no han reportado efectos significativos del tempo musical sobre el desempeño de los conductores [42] [28] [45] [33] [46], e inclusive los efectos han sido positivos [34].…”
Section: Categorías De Análisis Del Contenido De Las Publicacionesunclassified
“…Son on beş yılda en popüler işitsel uyaranlardan biri olan araç kullanırken müzik dinlemek, başlangıçta çoğunlukla bir dikkat dağıtıcı olarak ele alınmıştır (Brodsky ve Slor, 2013;Ünal, Steg ve Epstude, 2012). Araç kullanırken müzik dinlemek çoğunlukla ikincil bir görev olarak ele alınmış; müzik dinlemenin sürücü performansına olan etkisi, gerçek zamanlı araç kullanma (Brodsky ve Slor, 2013), simülasyon (Brodsky, 2001;Febriandirza, Chaozhong, Zhong, Hu ve Zhang, 2017;Hughes, Rudin-Brown ve Young, 2013;Ünal, de Waard, Epstude ve Steg, 2013; van der Zwaag ve ark., 2012) ve oyun çalışmaları (Cassidy ve MacDonald, 2010;North ve Hargreaves, 1999) ile incelenmiş; zihinsel çaba (Ünal ve ark., 2012), görev zorluğu (Wang, Jimison, Richard ve Chuan, 2015) ve araç kontrolü (Brodsky, 2001) gibi farklı değişkenler ile birlikte araştırılmıştır. Sürücülük ve araç kullanırken müzik dinlemek ile ilgili alan yazının sunduğu genel çerçeve, araç kullanırken müzik dinleyen sürücülerin daha yavaş araç kullandığını (Hughes ve ark., 2013) ve daha fazla trafik ihlalinde bulunduklarını ortaya koymaktadır (Brodsky, 2001).…”
Section: Araç Kullanırken Müzik Dinlemekunclassified